The long-run real effects of banking crises: Firm-level investment dynamics and the role of wage rigidity - Carlo Wix (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
This paper studies the long-run effects of credit market disruptions on real firm outcomes and how these effects depend on nominal wage rigidities at the firm level. I trace out the long-run investment and growth trajectories of firms which are more adversely affected by a transitory shock to aggregate credit supply. Affected firms exhibit a temporary investment gap for two years following the shock, resulting in a persistent accumulated growth gap. I show that affected firms with a higher degree of wage rigidity exhibit a steeper drop in investment and grow more slowly than affected firms with more flexible wages.
urn:nbn:de:hebis:30:3-451947
Keywords: E22; E24; E51; G01; G21; G31; 330; Financial Crises; Bank Lending; Real Effects; Firm Investment; Wage Rigidity; Labor Hoarding